3D numerical modelling and simulation of the impact of fault zones on fluid flow in sandstones of the Rio do Peixe Basin, NE Brazil. Issue 4 (2022) - Stohler, Rômulo C.; Nogueira, Francisco C. C.; Mello, Claudio L.; Souza, Jorge A. B.
No abstract available